ECONOMIC REFORMS IN THE UZBEKISTAN CONSTRUCTION INDUSTRY: STATUS AND DEVELOPMENT STRATEGIES (Marketing Journal, 2025)
This article explores the role and significance of the construction sector in the economy of the Republic of Uzbekistan, emphasizing the critical impact of investments on sustainable development. It analyzes the sectorʼs integration with other industries, its influence on GDP, fixed assets, and employment. Legal frameworks and academic research are referenced to justify the need for effective investment management in the construction field.
Keywords: construction sector; investments; gross domestic product; fixed assets; economic growth; sustainable development; employment